The NTP-binding Motif in Cowpea Mosaic Virus B Polyprotein is Essential for Viral Replication - Peters, Sander A.; Verver, Jan; Nollen, Ellen A. A.; van Lent, Jan W. M.; Wellink, Joan; van Kammen, Ab (Journal of General Virology, 1994)
We have assessed the functional importance of the NTP-binding motif (NTBM) in the cowpea mosaic virus (CPMV) B-RNA-encoded 58K domain by changing two conserved amino acids within the consensus A and B sites (GKSRTGK500S and MDD545, respectively). Both Lys-500 to Thr and Asp-545 to Pro substitutions are lethal as mutant B-RNAs were no longer replicated in cowpea protoplasts. Transiently produced mutant proteins were not able to support trans-replication of CPMV M-RNA in cowpea protoplasts in contrast to transiently produced wild-type B proteins. Therefore loss of viral RNA synthesis was a result of a protein defect rather than an RNA template defect. Mutant B polyproteins were correctly processed in vitro and in vivo and the regulatory function of the 32K protein on processing of B proteins was not affected by these mutations. Since regulation of processing by the 32K protein depends on interaction with the 58K domain, the mutations in the NTBM apparently do not interfere with this interaction. The Asp-545 to Pro substitution left intact the binding properties of the 84K precursor of the 58K protein, with respect to ATP-agarose, whereas the Lys-500 to Thr substitution decreased the binding capacity of the 84K protein, suggesting that the Lys-500 residue is directly involved in ATP binding. The Lys-500 to Thr substitution in the 58K domain resulted in an altered distribution of viral proteins, which failed to aggregate into large cytopathic structures as observed in protoplasts infected with wild-type B-RNA. However viral proteins containing the Asp-545 to Pro substitution showed a normal distribution in protoplasts.